Gastric antral vascular ectasia. Clinical presentation and therapeutic management - Nélcido Luis Sánchez García; Ulises Periles Gordillo; Frank Pérez Triana; Yoandy Hernández Casas; Alfredo Hierro González (Medisur, 2018)
Gastric antral vascular ectasia is an infrequent cause of high gastric hemorrhage, responsible of the 4% of high gastric non-variceal hemorrhages. The diagnosis is based on endoscopic findings and its most accepted treatment is argon plasma coagulation. It is presented a case of a woman with recurrent digestive hemorrhages in the form of melena and anemia, who was performed a high digestive endoscopy with resulting a diagnosis of vascular ectasia of the gastric antro. Later she was treated satisfactorily with argon plasma coagulation without complications. The resent work is aimed at reviewing an unusual cause of digestive bleeding and its treatment.